Comparison of Frequency of Union with Percutaneous Intramedullary Kirschner Wire versus Interfragmentary Screw Fixation in Displaced Extra-articular Metacarpal Fractures - Farhan Qazi, Majid Zaheer, Zubair Khalid, Hafiz Iftikhar Ahmed Sadaqat, Muhammad Umar Hafeez, Amanullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the frequency of union in cases treated with percutaneous intramedullary kirschner wire versus interfragmentary screw fixation of displaced extra-articular metacarpal fractures. Study Design: Randomized controlled trial. Place and Duration: The Department of Othropedic surgery, Ghurki Trust Teaching Hospital Lahore, Pakistan from May 2021 to November 2021. Methodology: A total of 70 cases (35 in each group) of both genders aged 18-60 years with displaced extra-articular metacarpal fracture were included. Surgery was performed with the patient under peripheral anesthesia adopting pneumatic tourniquet and image intensification. Patients were randomly divided into 2 groups, undergoing either percutaneous intramedullary K-wire fixation or interfragmentary Screw Fixation. Patients were followed up till 16th week to see the union. Results: The mean age of patients in K-wire group was 37.89±9.34 years and in screw fixation group was 40.17±12.82 years. In K-wire group, there were 24 (68.57%) male and 11(31.4%) female cases while in Screw fixation group there were 17 (48.6%) male and 18 (51.4%) female cases. In K-wire group, 20 (57.1%) cases reported union while in Screw fixation group, 33 (94.3%) cases reported union at the final follow up (p<0.001). Practical Implications: Interfragmentary screw fixation in displace extra-articular metacarpal fractures yielded better outcomes. Conclusion: Significantly more cases treated with interfragmentary screw fixation of displaced extra-articular metacarpal fractures reported union in comparison to percutaneous intramedullary kirschner wire. Keywords: Metacarpal fractures, internal fixation, intramedullary K-wire, screw fixation, union.